Venous plasma serotonin is not a proper biomarker for pulmonary arterial hypertension. (April 2014) - Zeinali, Fatemeh; Hauso, Øyvind; Wiseth, Rune; Moufack, Marcel; Waldum, Helge L.
Abstract Objectives. Serotonin (5-HT) most likely plays an important role in the pathogenesis of pulmonary arterial hypertension (PAH). We aimed to test if venous plasma 5-HT is a potential biomarker of PAH. We also measured venous blood β-thromboglobulin (β-TG) in all participants to ensure that any increase in serotonin levels measured is due to platelet release. Design. Blood samples from patients (n = 9) with pulmonary arterial hypertension (Group 1 of the World Health Organization classification of pulmonary hypertension) as well as healthy volunteers (n = 9) were analyzed. We used enzyme-linked immunosorbent assay (ELISA) to measure venous platelet-poor plasma 5-HT and β-TG in patients with pulmonary arterial hypertension (PAH) and in age-matched normal controls. Results. Venous platelet-free plasma 5-HT and β-TG were almost similar in patients with PAH and healthy controls with only a slight trend toward increased 5-HT levels in patients with PAH. No correlation was found between venous platelet-poor plasma 5-HT and disease severity. There was no association between venous plasma 5-HT and the mean pulmonary artery pressure. Conclusions. Our data suggest that 5-HT is not significantly elevated in venous platelet-free plasma in patients with PAH and may accordingly not be a useful biomarker in this condition.